Correlation Between Leg Length, Arm Length, and Leg Muscles: Amateur Athlete's Basketball Under Shoot Skills - Munir, Ali (LPPM Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Improving the movement of basketball under shoot skills has several important component factors that need to be understood, one of which is the length of the legs, the length of the arms, and the explosiveness of the leg muscles. The purpose of this study is to analyze the correlation between arm length, leg length, and leg muscles on the results of basketball under shoot technique skills in amateur athletes at SMA Negeri 1 Sukoharjo. This type of research is a type of correlation research, and the population in this study is 20. Because the basis for determining the sampling of the researcher uses total sampling, so the samples in this study amounted to 20 samples. The data collection technique uses a measurement test, where in the variables of limb length and arm length use a measuring tape test instrument with a validity value of 0.877 and reliability of 0.786 and on the variable of leg muscles using a vertical jump test instrument. The data analysis technique in this study uses regression analysis and conducts prerequisite tests, linearity tests, and hypothesis tests using the help of SPSS version 26. The results of the study found that there was a significant relationship in all three variables to the results of under shoot basketball skills. Which is the relationship between the legs and legs to the results of under shoot basketball skills with a calculated value of 0.868. Furthermore, there is a relationship between arm length and the result of under shoot basketball skills with a calculated value of 0.650. And there is a relationship between leg muscles and the results of under shoot basketball skills with a calculation value of 0.748. Based on the results of the study, it can be concluded that limb length is the most important component in order to get maximum results from the under shoot technique. So that this can be used as a reference by coaches so that they can provide the right training treatment to optimize the length of the athlete's limbs in order to obtain the expected achievement